Neposredna in posredna odgovornost upravljavcev spletnih platform zaradi kršitve znamke: Primary and Secondary Liability of Online Platform Operators for Trademark Infringement - Repas, Martina (Digital Platforms: Legal And Economic Challenges, 2024)
The article deals with three aspects of the liability of online platform operators due to trademark infringements: primary liability based on Directive 2015/2436, secondary liability based on Directive 2000/31 or, today, Regulation 2022/2065, and taking measures to prevent further violations under Directive 2004/48. For this purpose, it analyzes the decisions of the CJEU in which their liability was discussed and, in particular, highlights the primary liability and the decision in the Louboutin case. In this decision, the CJEU extended the primary liability of the operator of the online platform for trademark infringement compared to previous cases. The authoress notes, however, that this decision does not mean a move towards stricter liability of online platform operators, but that the characteristics or particularities of the facts of the case (which were significantly different from previous cases) were those that led to the establishment of their primary liability.